PRINCIPLES OF DEVELOPING STUDENTS' MEDIA LITERACY AND INFORMATION CULTURE - Xamidova Feruza Shamsiddinovna (Modern American Journals, 2025)
This article discusses the issues of forming and developing media literacy and information culture among students. The content of the concept of media literacy, pedagogical and psychological principles of its development, as well as its importance in strengthening the student's conscious and critical thinking skills in the modern information space are analyzed.
Keywords: Media literacy, information culture, principles, students, critical thinking, information security.